Ethic imagination in architecture - Almaamouri, Abdullah Saadoon Salman; Hameed, Tuqa Mahmood (Iraqi Journal of Architecture and Planning, 2018)
Research examines the concept of ethical imagination as one of the influential concepts in the architectural design process. Who is known as "the Architect’s ability to think according to moral frameworks to become an important source and then to be the task of balancing the poetic and the disciplined imagination to produce an ethical architectural text that benefits the individual and society.", thus be the research problem (implications of morally imaginative concept in architecture ).So the research aims to explain the basics of moral fiction in architecture, and we are on it. Research assumes that the foundations of moral fiction have an impact on the formulation of the architectural product . For the purpose of addressing the research issue and achieving the objectives of research and verification of its hypothesis, a knowledge framework was first built .Then a comprehensive theoretical framework for the imagination of the moral architecture extracted from the architectural propositions to be finalized in three main indicators is. Principles of moral constructional imagination, the foundations of moral and ethical imagination, moral logic of the Moral imagination architecture. Then apply them to elected projects to illustrate their impact on the architectural output and to arrive at conclusions that show the architectural imagination according its basics